2018
DOI: 10.1111/jog.13670
|View full text |Cite
|
Sign up to set email alerts
|

Enclosing sutures technique for control of local bleeding in a case of placenta increta

Abstract: Antepartum diagnosis of uterine placenta increta is difficult, thus considering a counterplan during placental delivery is obliged. Uterine compression suture is one of the choices of hemostatic surgical techniques for postpartum hemorrhage. However, uterine synechiae/ischemia are known for the complications. To avoid these complications, we performed a novel hemostatic suture with a contrivance for a case of uterine posterior placenta increta. A nullipara with a history of multiple intrauterine operation unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…This surgery stop the bleeding without penetrating the endometrium, affecting lochia discharge, avoiding intrauterine adhesion, and there is no change of menstruation in the patients during follow‐up. Compared with the previous modified surgical procedure, our suture method can avoid abdominal adhesion to a greater extent 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This surgery stop the bleeding without penetrating the endometrium, affecting lochia discharge, avoiding intrauterine adhesion, and there is no change of menstruation in the patients during follow‐up. Compared with the previous modified surgical procedure, our suture method can avoid abdominal adhesion to a greater extent 31 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous modified surgical procedure, our suture method can avoid abdominal adhesion to a greater extent. 31 The incidence of severe PPH that could not be uncontrolled by drugs and traditional methods is relatively low. Therefore, when severe PPH occurs, they often do hysterectomy to save patients' lives in some primary hospitals because of the lack of relative equipment.…”
Section: Discussionmentioning
confidence: 99%
“…For severe hemorrhage from the surface of the placental separation in cases of placenta previa or placenta accreta, pressure hemostasis with gauze and suture hemostasis have been performed commonly, but these procedures are often unsuccessful in the presence of bleeding from a large area. Although separation of the bladder may be necessary on the anterior wall, the use of a simple suture or Z-suture, piercing the whole myometrium at several sites [3]; a large U-shaped suture; an interrupted circular suture consisting of repeated simple sutures in the entire circumference of the anterior and posterior walls [14]; and a suture of the muscular layer to block blood flow in four directions has been reported [3,14,15]. On the other hand, Bakri [16] reported that uterine balloon tamponade was effective for controlling hemorrhage from the surface of separation of the placenta previa.…”
Section: Hemostasis For the Surface Of The Placental Separationmentioning
confidence: 99%
“…When hemorrhage from the placental separation surface was severe, pressure hemostasis with gauze and suture hemostasis were commonly employed but often unsuccessful in cases with bleeding from a large area. Although separation of the bladder may be necessary on the anterior wall, the use of a simple suture or a Z-suture piercing the entire myometrium at several sites, a large U-shaped suture, enclosing sutures 21) and an interrupted circular suture 22) consisting of repeated simple suturing of the entire circumference of the anterior and posterior walls, have been reported.…”
Section: Hemostasis In Cesarean Section 1) Hemostasis For the Placentmentioning
confidence: 99%